Pengaruh Kepuasan Kompensasi dan Lingkungan Kerja terhadap Kinerja Karyawan dengan Motivasi Kerja sebagai Variable Intervening: Studi pada Perusahaan PT. Southern Chemicals & Engineering - Amanda Herbudiarti; Indi Djastuti (Diponegoro Journal of Management, 2026)
This study aims to determine and analyze the effect of Compensation Satisfaction and Work Environment on Employee Performance with Work Motivation as an intervening variable at PT. Southern Chemicals & Engineering, North Jakarta. The population in this study consisted of all permanent employees, with a total sample of 89 respondents selected using the total sampling technique. Data were collected through a questionnaire using a five-point Likert scale and analyzed using the SEM-PLS (Structural Equation ModelingPartial Least Squares) method with the assistance of SmartPLS version 4 software to examine the direct and indirect relationships among variables. The results of the study indicate that compensation satisfaction has a positive and significant effect on employee performance as well as on work motivation. The work environment has a positive and significant effect on work motivation; however, it does not have a direct significant effect on employee performance. Work motivation has a positive and significant effect on employee performance. Furthermore, work motivation is proven to mediate the effect of compensation satisfaction and work environment on employee performance.